Case reportAngioneurotic edema: a rare case of hypersensitivity to metoclopramide - Pietrzko, Paweł; Zakrzewski, Aleksander; Matuszewski, Tomasz; Kruszewski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
The case of a 30-year-old woman who had already experienced two incidents of angioneurotic edema and urticaria caused by drugs during the acute gastroenteritis. The allergological workup revealed hypersensitivity to metoclopramide. This case documents that metoclopramide, a drug commonly used to inhibit the vomiting, may cause not only bronchospastic reaction in an asthmatic patient but also angioneurotic edema of the tongue and larynx as well as urticaria. No similar cases in the literature were found.